Comparison of the effectiveness of spiritual intelligence training based on quranic teachings and spiritual intelligence training based on bowell\'s view on students\' psychological well-being - marzieh sherkat; mehrdad kalantari; masoud Azarbayejani; Mohamad Reza Abedi (مجله علوم روانشناختی, 2020)
Background: Previous studies have examined the effectiveness of spiritual intelligence on psychological well-being. But there is a research gap between comparing the effectiveness of spiritual intelligence education based on Qur'anic teachings and spiritual intelligence education based on Bowell's view of students' psychological well-being. Aims: The purpose of the present study was to compare the effectiveness of spiritual intelligence training based on Quranic teachings and spiritual intelligence training based on Bowell's view on psychological well-being of Isfahan students. Method: The research was quasi-experimental with pretest, posttest, followup with control group (unequal groups). The statistical population included all students of the University of Isfahan (15171 people) in the academic year 2017-2018. Fifty-five of these students were randomly selected as random samples and 40 randomly assigned to experimental groups (20 in the group based on Quranic teachings and 20 in the Bawl perspective group) and 15 in the control group. Were replaced. The tools of the present study are: sessions of teaching spiritual intelligence based on Quranic teachings (2020), teaching spiritual intelligence based on Bowl's point of view (2004) and Riff's psychological well-being questionnaire (1989). Data analysis was performed using covariance analysis method. Results: Both spiritual intelligence trainings based on Quranic teachings and based on Bowl's view had a significant effect on students' psychological well-being (P< 0/05). There was no significant difference between the two views in terms of the effect on psychological well-being (P< 0/05). Conclusions: Students who participated in the teaching of spiritual intelligence based on Quranic teachings and the teaching of spiritual intelligence based on Bowl's view gained higher psychological well-being.